مواقف محب الدين الخطيب من القضايا السياسية والعسكرية في شبه الجزيرة العربية 1926-1948م - الشريف، حسين محمد (جامعة محمد بوضياف المسيلة - مخبر الدراسات والبحث في الثورة الجزائرية, 2021)
After the end of the first world war in november 1918, by the truce signature between England with its allies and the Ottoman empire, the dream of the great Arab country had evaporated because of England and France’s plans. The British soon implemented their colonial scheme of dividing the levant countries. Only the Arabian peninsula with cutted edges came through this plan, where every prince retained what he seized of lands during the war. Cherif Hussein was a King on Hidjaz, Abdelaziz Ben Saoud a King of Nadjad. They got into a war between them because each of them wanted Alhidjaz for himself. Al Khatib was angry with the hashemites because they asked the British to support them in 1924. The Saoudians won the war and they constructed their country on Islamic bases. Mohebedine Al Khatib was very impressed by this achievement and he consideled it an Islamic victory and the best response to turkey laîc apostasy on Islamic principles.
بعد انتهاء الحرب العالمية الأولى في نوفمبر 1918م بتوقيع الهدنة بين إنجلترا وحلفائها وبين الدولة العثمانية، تبخر حلم الدولة العربية الكبرى بما بينته إنجلترا وفرنسا للعرب. سرعان ما نفذ الإنجليز مخططهم الاستعماري بتقسيم بلاد المشرق العربي. ولم ينج من ذلك إلا شبه الجزيرة العربية المقصوصة الأطراف والتي احتفظ فيها كل أمير بما استولى عليه من أراض أثناء الحرب. فكان الشريف حسين ملكا على الحجاز، وعبد العزيز بن سعود أميرا على نجد... وغيرهما، اللذان دخلا في حرب فيما بينهما لأن كل واحد منهما يريد الاستيلاء على الحجاز لوحده. وقد حز في قلب الخطيب دعوة الهاشميين الإنجليز للوقوف إلى صفهم عام 1924م ضد السعوديون. انتصر السعوديون في هذه الحرب وأقاموا دولتهم على أسس إسلامية. وقد أعجب محب الدين الخطيب بذلك إعجابا شديدا واعتبره نصرا للإسلام وشريعته. وهو أحسن رد على ما قامت به تركيا العلمانية من ردة على مقومات شخصيتها الإسلامية.
Keywords: الصراعات السياسية -- القضايا العسكرية -- تاريخ السعودية -- الخطيب، محب الدين بن أبي الفاتح، ت. 1969 م